2008
DOI: 10.1007/s10620-008-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a New Therapeutic Regimen Versus Two Routinely Prescribed Treatments for Eradication of Helicobacter Pylori: A Randomized, Double-Blind Study of Doxycycline, Co-Amoxiclav, and Omeprazole in Iranian Patients

Abstract: This study compared a new regimen (group A: doxycycline, co-amoxiclav, omeprazole) and two routinely prescribed regimens (group B: amoxicillin, omeprazole, furazolidone, bismuth; group C: amoxicillin, clarithromycin, omeprazole) to find an acceptable first-line treatment option for Helicobacter pylori. The study population consisted of 189 patients who referred to our clinic to undergo endoscopy due to ulcer-like dyspepsia. The H. pylori eradication rate was 68% in group A, 56% in group B, and 70% in group C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…These results are similar to those observed in the works of Bellelis [20], and Coelho [22] in research studies also conducted in Brazil. Results in works from Taiwan [23], Kuwait [24], Hong Kong [25], Iran [26], and Chile [27] have presented similar results regarding the efficacy of triple therapy. Metaanalysis of published works regarding the differences between the PPI in H. pylori treatment regimens showed eradication rates between 82% and 84% when they were combined with amoxicillin and clarithromycin [15,16].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results are similar to those observed in the works of Bellelis [20], and Coelho [22] in research studies also conducted in Brazil. Results in works from Taiwan [23], Kuwait [24], Hong Kong [25], Iran [26], and Chile [27] have presented similar results regarding the efficacy of triple therapy. Metaanalysis of published works regarding the differences between the PPI in H. pylori treatment regimens showed eradication rates between 82% and 84% when they were combined with amoxicillin and clarithromycin [15,16].…”
Section: Discussionmentioning
confidence: 67%
“…Upper digestive endoscopy was performed in all patients for peptic ulcer identification and gradation according to the Sakita classification [26], and H. pylori status was determined through rapid urease test and histological examination through a modified Giemsa staining method performed on gastric mucosa samples obtained from the antrum and corpus.…”
Section: Methodsmentioning
confidence: 99%
“…In the study from Texas [3] , 5 substudies have been performed, comparing the same doxycycline regimen with 5 different regimens without doxycycline. The studies from Italy, Iran and New York [6,8,10] ( table 1 ) [2,3,6,10] . In 5 sub-studies, treatment regimens with doxycycline had significantly higher eradication rate than treatment regimens without doxycycline ( table 1 ) [3,6,10] .…”
Section: Resultsmentioning
confidence: 99%
“…Out of three 7-d regimens, 1 study showed acceptable eradication rates [19][20][21] . Also, out of three 10-d regimens, 2 were successful in achieving > 90% PP eradication rate [22][23][24] and out of three 14-d regimens, 1 yielded optimal results [25][26][27] .…”
Section: Standard Triple Therapymentioning
confidence: 99%
“…Furazolidone has been used in nine quadruple therapies in Iran [23,27,[47][48][49][78][79][80][81] , four of which showed optimal efficacy, although severe side effects were reported in 14-d regimens. Low dose Furazolidone was used in a further study, which led to significant decline in eradication rate [80] .…”
Section: Furazolidonementioning
confidence: 99%